PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL FLIPBOOK MENGGUNAKAN APLIKASI CANVA DALAM PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR - Reni Rahmawati; Indhira Asih Vivi Yandari; Sukirwan Sukirwan; Aan Subhan Pamungkas (STKIP Persada Khatulistiwa Sintang, 2023)
This research is based on the problems found in students who have difficulty understanding thematic learning material and the lack of interest of students in learning is seen because during the learning process students only listen, see and record what is conveyed by the teacher. The results of research on the development of flipbook digital media are very useful and play an important role in learning activities at school so that students look enthusiastic and happy in learning. The purpose of this study was to determine the feasibility of the media and students' responses to digital flipbook learning media using the Canva application in thematic learning theme 3 sub-theme 2 healthy food for fifth grade elementary school students. This study uses the Research and Development (RnD) method according to Sugiyono with six stages of development namely potential and problems, data collection, product design, design validation, design revision, product trial (limited). The results of this study were 1) validation by media experts obtained an average of 89% in the very feasible category, validation by material experts obtained an average of 86.11% in the very feasible category and validation by linguists obtained an average of 79% in the feasible category; 2) the response of students as a whole obtains 95% in a very good category.